E02 Longitudinal Shape Analysis Study of Striatal Nuclei in Manifest Huntington's Disease. (17th September 2014) - Cleret de Langavant, L; Nazir, M; Gaura, V; Verny, C; Krystkowiak, P; Bachoud-Lévi, A-C; Remy, P
Abstract : Background: Huntington's disease (HD) is marked by brain degeneration in striatum. Localised atrophy identified through shape analysis of these structures was recently suggested to be a more sensitive biomarker of disease evolution than global volume variations (van der Bogaard et al ., 2011). Aims: To identify longitudinal changes in shape of striatal structures in a group of patients with manifest HD. Methods: In the Multicenter Intracerebral Grafting trial for Huntington's disease (MIG-HD), a group of 15 patients with manifest HD was followed-up during 20 months before intrastriatal grafting. The mean UHDRS Total Motor Score was 29.7 at first evaluation. T1-weighted brain MRIs of these patients were achieved at both the beginning and the end of this period. Segmentations of striatal nuclei (Freesurfer processing) were submitted to shape analysis using the SPHARM method (Brechbuhler et al ., 1995) which creates parametric surface models using spherical harmonics. Longitudinal changes in atrophy using shape analysis method was compared to global volumetric changes and voxel based morphometry (SPM8/VBM8). Results: Using global volumetric evaluation (Freesurfer) or voxel based morphometry (VBM), progressive atrophy was only found in left putamen during this period. However, using the SPHARM method, longitudinal shape analysis showed local atrophy in all striatal nuclei during the same period. Conclusions: Longitudinal shape analysis of striatum constitutes a promising tool to track Huntington's disease evolution and to better evaluate the benefits of innovative therapies in cohorts with small number of HD participants.